Strengthening Local Wisdom Value in Developing Religious Moderation - Fakhrul Rijal; Aria Sandra; Rafidhah Hanum; Tasnim Idris (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
Religious moderation is a measure or parameter which can be used as an indicator to measure whether an attitude and a person's way of behaving in religion belong to which group, moderate or extreme. This study aims to find out the values of local wisdom in Aceh Singkil, how they are formed, and their roles. Likewise, with the harmonization and moderation of religion, what exactly is the moderation of religion in Singkil, and what is the role of local wisdom in building harmony and moderation of religion in Singkil. This study uses a qualitative method to produce descriptive data and facts about the actual situation without any setting or manipulation of the conditions of the subjects studied. The form of local wisdom in building harmony between religious communities in Singkil is marked by the various interactions and social contacts they carry out in their daily lives in various forms, such as cooperation activities and other relationships. This harmony can occur because of mutual respect among them and does not bring religious issues into their lives. Good relations among them do not only occur in daily life but also in various other places such as markets, organizations, and so on.